Harsh words : English words for Chinese learners - Hill, Monica (Hong Kong University Press, 2005)
"Harsh Words provides a theoretical background explaining how words are learned and then focuses on the Chinese learner in particular. It covers vocabulary learning strategies, learning words in isolation as well as in context, testing vocabulary, common Chinese errors with words, and vocabulary activities to use in class. One chapter deals with the use of IT in vocabulary development and suggests web sites and software that teachers may want to use with their students. Each chapter contains tasks and revision questions while an answer key is provided at the end." "The book is written for teachers, whether training to be English teachers or taking refresher courses, postgraduate diplomas or Master's. While much of the content is applicable to all levels of learners, teachers in secondary schools and universities will find it most useful."--Jacket.